2002
DOI: 10.1162/003355302760193904
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Social Preferences with Simple Tests

Abstract: Departures from self-interest in economic experiments have recently inspired models of "social preferences". We design a range of simple experimental games that test these theories more directly than existing experiments. Our experiments show that subjects are more concerned with increasing social welfare-sacrificing to increase the payoffs for all recipients, especially low-payoff recipients-than with reducing differences in payoffs (as supposed in recent models). Subjects are also motivated by reciprocity: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

138
2,702
11
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 3,308 publications
(2,968 citation statements)
references
References 26 publications
138
2,702
11
8
Order By: Relevance
“…In an empirical test of Rawls's theory, Frohlich and Oppenheimer (1992) found that most participants preferred income distributions with the highest total payoff given a floor constraint; that is, a key consideration was to minimize the distance between the loser and others. Similarly, the size of the loser's share is a key component of Charness and Rabin's (2002) social welfare function. For ease of comparison, we can express their model in terms of differences between shares instead of absolute share sizes.…”
Section: Perceptions Of Unfairness In Allocationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In an empirical test of Rawls's theory, Frohlich and Oppenheimer (1992) found that most participants preferred income distributions with the highest total payoff given a floor constraint; that is, a key consideration was to minimize the distance between the loser and others. Similarly, the size of the loser's share is a key component of Charness and Rabin's (2002) social welfare function. For ease of comparison, we can express their model in terms of differences between shares instead of absolute share sizes.…”
Section: Perceptions Of Unfairness In Allocationsmentioning
confidence: 99%
“…To summarize, the model we propose takes into account both the general envy-based sense of unfairness of Varian (197699) and the loser-based sense of unfairness of Rawls (1999) and Charness and Rabin (2002).…”
Section: Perceptions Of Unfairness In Allocationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature in this area is expanding rapidly and so is variety of the proposed models. These models include both linear (such as Fehr and Schmidt 1999; Charness and Rabin 2002;Levine 1998;Rotemberg 2004;and Erlei 2004), and nonlinear models (such as Bolton and Ockenfels 2000;Cox et al 2004;Ottone and Ponzano 2005;and Cox et al 2007).…”
Section: Introductionmentioning
confidence: 99%